The Urgency of Immigration Intelligence in Anticipating Illegal Immigrants - Yahya Nuur Zaman; Ghozy Prananda Fakhruddin; Ahmad Rasyid Adenan (Fakultas Hukum Universitas Hang Tuah, 2023)
The arrival of illegal immigrants to an area is a threat to state sovereignty. This situation is certainly dangerous, considering that everyone who will enter the territory of a country must know the origin and destination. In dealing with these illegal immigrants, immigration has an important function in preventing and controlling illegal immigrants. This research will examine the position and role of immigration intelligence in overcoming the problem of illegal immigrants in Indonesia. The research method used in this study is normative juridical with a statutory, case, and conceptual approach. The results of the study found that immigration intelligence has an important role in maintaining national stability and overcoming national threats from the problem of illegal immigrants. Immigration Intelligence can act as a deterrent and controller for illegal immigrants. Currently, immigration intelligence has various programs in dealing with the problem of illegal immigrants, such as establishing a foreigner reporting system (APOA), forming an intelligence community consisting of law enforcement officials and government institutions, and cooperation with Interpol.